Garbhagriha of the Mahishasuramardini Temple (Temple 6) - Temples of India Project Team (Jio Institute, 2024)
Details of the antarala (vestibule) and entrance of the garbhagriha (sanctum sanctorum) of the Mahishasuramardini Temple (Temple 6), Baroli group of temples.